Heroic and Post-colonial Antarctic narratives - N. Brazzelli (Edward Elgar, 2017)
In 2012 the anniversary of Robert Falcon Scott’s arrival at the South Pole and of his death in the ice on his return journey has prompted new research on Scott and the Antarctic continent. The renaissance of Antarctic interests shows that Antarctica continues to be a source of fascination for the Western world as a place for the expression of individual bravery and endurance. However, the role of Antarctica as an imperial space in the British cultural imagination is now superseded by its status of postcolonial territory ‘owned’ both by the former imperial nations and by postcolonial countries such as India or New Zealand. Many other countries are directly involved in the project of making the ‘white continent’ a natural reserve entirely devoted to science. The contemporary process of creating Antarctica through writing is strongly linked to memorialization of the past including the ‘built’ environments of the continent, that is the scientific bases, the bodies of the people moving across or temporarily living on ice. A broad range of contemporary representations, discourses and practices that revive the Heroic Era rewrite, critique, constitute and imagine the cultural history and landscape of Antarctica, to provide a comprehensive understanding of the area’s fragile geopolitics.